The role of xylooligosaccharides in feed efficiency of non-ruminants - Dale, Tom (2020)
It has become increasingly common in non-ruminant animal production systems for the feed to be supplemented with exogenous fibrolytic enzymes, such as xylanase. This may help contribute to global food security by increasing the feed efficiency of livestock fed on poor quality diets. Fibrolytic enzymes, like xylanase, target the non-starch polysaccharide (NSP) fraction of feed. These have been reported to improve the growth characteristics of chickens, via various suggested mechanisms. Recently, there has been heightened interest in the xylooligosaccharides (XOS) that are generated by the hydrolysis of xylan with xylanase enzymes, which have been suggested to have prebiotic effects that ultimately may lead to improved bird health and growth characteristics. It is theorised that the XOS generated by enzymatic hydrolysis could be affected by the combination of enzymes and substrates present in different feed sources. Therefore, the aims of this thesis were as follows. 1) Identification of the xylo-oligosaccharide fingerprint of different feed sources digested with different exogenous xylanase enzyme products in vitro. 2) To further investigate and characterise the generation of XOS and monomeric substrates from different varieties of wheat when supplemented with an array of exogenous xylanase enzyme products. 3) To study the effects of xylanase supplementation on the growth performance, generation of XOS and related monomers in various locations of the gastrointestinal tracts of broilers fed a wheat-based diet in vivo and compare that to the in vitro digestion model used for previous works. An in vitro study investigated the range of XOS and monosaccharides produced from four cereal samples (barley, maize, oats and wheat) over a 72 hour in vitro incubation using 3 commercially (AB Vista) available fibrolytic enzymes Econase XT, Econase MP1000 and Barley P700, all containing endo-xylanase with other combinations of enzymes. There was a cereal x enzyme x incubation time 3-way interaction in the generation of XOS (xylotetraose, xylotriose and xylobiose) (P<0.01) indicating the generation of XOS varies dependent on both the cereal and the enzyme used. Econase XT generated the greatest quantity of xylose, with 38% of available xylose from wheat being released after 72 h, 11% from barley and 9% from oats. In a second in vitro experiment, it was investigated how different exogenous enzymes interact with different varieties of wheat. The generation of NSP-derived substrates including XOS and monosaccharides from six wheat varieties (Maris Huntsman, Highbury, Paragon, Sinuelo, Chinese Spring and Pavon 76) were measured, over a 24 hour in vitro incubation, with different commercially available fibrolytic enzymes. There were significant variety x enzyme x incubation time interactions for the release of xylobiose, galactose and glucose (all p<0.001) and significant enzyme x variety interactions for the release of xylotriose (p=0.022), xylose (p<0.001) and arabinose (p=0.028). A final study quantified xylanase-induced changes in soluble monosaccharides, XOS and volatile fatty acid (VFA) contents of the different sections of the poultry GIT and whether these relate to altered bird performance. To do this, an in vitro digestion of the wheat-based diet was carried out with xylanase (Econase XT at 16,000BXU/kg diet) to compare the in vitro and in vivo generation of these XOS and monosaccharides. For the in vivo study, 80 male Ross 508 broiler chicks were split into two groups fed a wheat-based diet with or without Econase XT (16,000BXU/kg diet) for 21 days. Although there were no effects of Econase XT inclusion on growth performance characteristics, supplementation increased the xylotetraose (X4) content in the colon (p=0.046, enzyme x GIT section interaction) and the xylose contents in the colon and caeca (p<0.001, enzyme x GIT section interaction). There was also a trend for increased acetate proportion in the caeca of Econase XT treated birds (p=0.062). These findings suggest that the fibrolytic enzymes tested in the present studies have some specificity for different cereals and for different varieties of wheat. Therefore, it may be possible to optimise the combinations of cereal varieties and enzymes used in animal feeds, to help maximise the feed efficiency of livestock. Also in vivo, the hydrolysis of wheat arabinoxylan in poultry is enhanced by xylanase supplementation, which may increase the production of beneficial VFA in the caeca, and thereby potentially modulate the caecal microbiome, although, this did not affect bird performance.